A multicentric, prospective study on oral and maxillofacial trauma in the female population around the world. Issue 3 (7th April 2022) - Romeo, Irene; Sobrero, Federica; Roccia, Fabio; Dolan, Sean; Laverick, Sean; Carlaw, Kirsten; Aquilina, Peter; Bojino, Alessandro; Ramieri, Guglielmo; Duran‐Valles, Francesc; Bescos, Coro; Segura‐Pallerès, Ignasi; et al.
Abstract: Background/Aims: Approximately 20% of patients with maxillofacial trauma are women, but few articles have analysed this. The aim of this multicentric, prospective, epidemiological study was to analyse the characteristics of maxillofacial fractures in the female population managed in 14 maxillofacial surgery departments on five continents over a 1‐year period. Methods: The following data were collected: age (0–18, 19–64, or ≥65 years), cause and mechanism of the maxillofacial fracture, alcohol and/or drug abuse at the time of trauma, fracture site, Facial Injury Severity Scale score, associated injury, day of trauma, timing and type of treatment, and length of hospitalization. Results: Between 30 September 2019 and 4 October 2020, 562 of 2387 patients hospitalized with maxillofacial trauma were females (24%; M: F ratio, 3.2:1) aged between 1 and 96 years (median age, 37 years). Most fractures occurred in patients aged 20–39 years. The main causes were falls (43% [median age, 60.5 years]), which were more common in Australian, European and American units ( p < .001). They were followed by road traffic accidents (35% [median age, 29.5 years]). Assaults (15% [median age, 31.5 years]) were statistically associated with alcohol and/or drug abuse ( p < .001). Of all patients, 39% underwent open reduction and internal fixation, 36% did not receive surgical treatment, and 25% underwent closed reduction. Conclusion: Falls were the main cause of maxillofacial injury in the female population in countries with ageing populations, while road traffic accidents were the main cause in African and some Asian centres, especially in patients ≤65 years. Assaults remain a significant cause of trauma, primarily in patients aged 19–64 years, and they are related to alcohol use.